Supporting Child Growth and Development with Balanced Nutrition: A Program of Nutritious Food Distribution and Nutrition Education through Pre-Test and Post-Test in Karangjambu Village as a Stunting Prevention Effort in Kebumen Regency - Yulianur, Hestina; Salsabilah, Siti Luthfiyah; Puand, Gandring Guste; Amanah, Masna Amelia; Pangestu, Antoni Budi; Kinanthi, Sekar; Bening, Bintang Cahya; Redianto, Evan Dwi; Qonita, Najwa; Atri, Afiza Widya Nur; et al. (Proceedings Series on Social Sciences & Humanities, 2025)
Kebumen Regency has demonstrated a significant decline in stunting prevalence over recent years; however, several villages continue to face elevated stunting rates, including Karangjambu Village, which has been designated as a priority area for stunting prevention efforts. This village holds substantial potential for community empowerment through health education programs, particularly targeting mothers of young children. This study aims to enhance the knowledge and awareness of mothers in Karangjambu Village regarding balanced nutrition and stunting prevention through a nutrition education program conducted at PAUD Anak Ceria. The method employed a direct and continuous approach comprising three phases: coordination with relevant stakeholders, face-to-face counseling supported by audiovisual media, and evaluation of learning effectiveness using pre-test and post-test assessments. Twenty mothers of children under five actively participated in the program. The evaluation results indicated a significant increase in knowledge, with pre-test scores varying between 30-60% and post-test scores ranging from 70-95%. The interactive, participatory education approach, complemented by practical demonstrations of nutritious meal preparation, proved effective in improving mothers’ understanding of the importance of balanced nutrition for child growth and stunting prevention. This program lays a strong foundation for empowering families to implement appropriate nutrition caregiving practices as part of sustainable efforts to reduce stunting incidence in the village.